Vzorci kljubovanja in čustvovanja v Prudencijevem Mučeniškem vencu - Pobežin, Gregor (Bogoslovni vestnik, 2024)
This paper examines a handful of poems from Prudentius’ poetic collection Peristephanon (“Crown of Martyrs”), with a particular focus on recurring patterns that are consistently present across the individual poems. The Peristephanon is a combination of pagan poetic metres and Christian content, addressing a very specific audience in the post-Constantinian period, at a time when the memory of the persecution of Christians under Diocletian was beginning to fade. The horrific scenes of bloody torture and the heroically exhilarating, almost joyful suffering of Christ’s soldiers – witnesses to his torment – were brought before the eyes of the readers in the elaborate, colourful poetic meters developed by pagan poetry, which has a special communicative value, but it also raises the question of purpose and effect. The individual hymns follow a predictable thematic pattern that invokes a rhetorical impression, but within the individual phases of the Passions we also encounter a number of other thematic correspondences or patterns.
Keywords: emotional patterns; Mučeniški venec; Peristephanon; Prudentius Clemens, Aurelius; the passion of martyrs; trpljenje mučencev; vzorci čustovovanja